Corporate social responsibility:An analysis of current practices in the hotel industry. - Mansor , Fazreena; Baba, Ismail (Universiti Sains Malaysia, 2014)
The fame of corporate social responsibility (CSR) is undeniable and many concerned hotels have already performed CSR practices. Therefore, the purpose of this study is to analyze and identify the current CSR practices by the worldwide hotels and specifically investigate the status and trend of CSR in the hotel industry.